Prince n Princess Bookstore & Cofeee House / Abdul Qayum Abdul Razak… [et al.] - Abdul Razak, Abdul Qayum; Mohd Kamil, Azmila; Mohd Razally, Nor Hidayah; Mat Zahari, Zarifah; Mohd Alwet, Hafizul Ashraf
In every progressive firm or organization, top management is really important to responsible for setting quantifiable, measurable and attainable objectives. This is to make sure the top management of the company can achieve there objective smoothly. For “PRINCE n PRINCESS BOOKSTORE & COFFEE HOUSE” our policy is developed as a guideline for daily operation of the company that stresses more on the continual need to maximize profits in a just, reasonable manner. Apart from trying to earn a fair return on investment from our stockholders. Other than that, we also are looking forward to improve our share in the market size. In addition, we will try to providing our customers with the best and fastest service to make sure our customers really satisfied with our company. In addition, to achieve our objective, we had determined our target market. As our company is located at campus zone or student zone, so our target markets are mostly among the student and lecturer. So this is our good opportunity corresponding to our objective to earn the greatest possible profit by increasing our service and offered a reasonable price to our customer. A related objective of the marketing department is to develop appropriate marketing strategies to ensure the transactions of the business are well done. Another important section in is Administration Plan. The main objective of the administrative office manager is to coordinate and communicate the information activities of each of the company’s main division so that unit costs of production may be reduced and productivity be increased. Therefore, in our company, administrative office manager provides a support service for all other functions. The most important part in our company is the cost of the project. Although every part of top management is really good, the project cost budget is the most important. This is because, if our capital can not support the business, this project will be useless. So, the total amount to start the project is RM 428,545.00 which less than our company capital; RM 600,000.00.